Selfish intentions: Kansas women and divorce in nineteenth century America - Schmidt, Janeal (Kansas State University, 2009)
In the United States, legal authorities well into the 20th century wanted to maintain the integrity of the marriage union; therefore, early divorce laws made it difficult to get divorced. When two individuals, a man and a woman, signed a marriage contract, their identities as two individuals became secondary to their identities as husband and wife. The “unit” established by the marriage was now a matter of public interest and of greater social importance than either individual. Legally, legislatures writing the laws and the courts enforcing them therefore did their best to maintain this unit. When one member of the unit petitioned for divorce, in effect they were claiming the actions of the other member of the unit had violated the legal and sacred bonds of that unit. In the late 19th century, western states, including Kansas began to make more liberal provisions for divorce. This study will examine those liberal divorce laws in Kansas with a particular focus on women who, like the Populist orator Mary Elizabeth Lease, used the law to protect their individual property interests in a marriage. Though such women were by no means the majority of women who sought divorce, their cases highlight a growing controversy in late nineteenth century Kansas over the state’s provisions for divorce. The openness of the state’s divorce laws allowed individuals, including female individuals, to use the law for their own purposes. Faced with the staggering increase in the Kansas divorce rate by the end of the century, some judges complained that the law did not adequately protect the state’s interest in preserving marital unions. To date, the historiography on divorce has focused on nation-wide trends. By focusing on Kansas law and the experience of women in the north central part of the state, this study seeks to open up an analysis, not just of the law, but of how individuals used the law. Chapter One includes a discussion on the evolution of divorce law in the United States. Chapter Two focuses on Kansas law and examines the uses that two particular women made of that law to act on their own behalf. Chapter Three examines the growing controversy in the late nineteenth century Kansas regarding the rising divorce rate and uses a controversial Clay County case to highlight some of the judicial concerns about the “abuses” of the law.
Keywords: Kansas; Women; Divorce; Law; Clay County; History; History, United States (0337)